Artemis Fowl : the graphic novel - Colfer, Eoin.; Donkin, Andrew; Lamanna, Paolo; Rigano, Giovanni (New York : Hyperion Books for Children, 2007)
A graphic novel adaptation of Eoin Colfer's novel in which a twelve-year-old evil genius tries to restore his family fortune by capturing a fairy and demanding a ransom in gold; but the fairies fight back with magic, technology, and a particularly nasty troll.
"Adapted from the novel Artemis Fowl"--Colophon.
Booklist
5.9
5-8.
5-8
Keywords: Fairies -- Comic books, strips, etc -- Juvenile fiction; Kidnapping -- Comic books, strips, etc -- Juvenile fiction; Magic -- Comic books, strips, etc -- Juvenile fiction; Mothers and sons -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Fairies -- Fiction; Fantasy; Kidnapping -- Fiction; Magic -- Fiction; Mothers and sons -- Fiction; Comic books, strips, etc; Fairies -- Comic books, strips, etc -- Fiction; Kidnapping -- Comic books, strips, etc -- Fiction; Magic -- Comic books, strips, etc -- Fiction; Mother-son relationship -- Comic books, strips, etc -- Fiction; England -- Comic books, strips, etc -- Juvenile fiction; England -- Fiction; England -- Comic books, strips, etc -- Fiction; Fantastic fiction; Fantasy comic books, strips, etc; Graphic novels